Ethnic advertising: adolescents' attitudes towards target and non-target advertisements - Muhammad Mohsin, Butt; Ernest Cyril, de Run (Emerald Group Publishing Limited, 2010)
Purpose – This article aims to explore attitudinal and behavioural differences between target and non‐target groups of ethnic advertisements. It seeks to expand the existing body of knowledge by investigating these differences from the perspective of young consumers in an Eastern context. This helps in testing the established theories of distinctiveness and cultural schemas in an Eastern society.